Infeminations: Exemplary (di)visions of the feminine in George MacDonald and Yasunari Kawabata. - Ceri Louise Mills (2004)
George MacDonald is a nineteenth-century Scottish writer. Yasunari Kawabata is a twentieth-century Japanese writer. This immediate disparity, coupled with their shared biological maleness, serves to make the authors' writings potentially fruitful for the infemination reading. This strategy, the infemination reading, simply, considers a male writer's negative constructions/conceptualisations of femininity. In my introductory 'Informulations' I define the infemination theorem, contextualising it as a derivative of the 'French feminist drawing on deconstruction' project. Here, I also outline my intention to consider the textual objects of analysis as autonomous, decontextualised entities. Following this, focus shifts from the theoretical text of infemination to the fictional texts (especially Lilith and Phantastes) of MacDonald, His specific infeminatory '(Di)Visions/Perversions of the feminine' are bisected as 'GynoScapes' (Chapter One) and 'GynEscapes' (Chapter Two). The former images a psychoanalytic penetration of 'infant' (infeminator) into the textual bodyscape of the 'mother'. The latter signifies literally 'an escape from the womb', and here penetrative desire becomes penetrative anxiety so that the infeminator endeavours to evade (re)union with her body. Kawabata's particular '(Di)Visions/Revisions of the feminine' are deemed 'HIStory' and 'HERstory'. These chapters share a concern with themes of language and silence. According to 'History' (Chapter Three), man constructs woman in the silence-inducing language of patriarchy. According to 'HERstory' (Chapter Four), woman strives to reclaim selfvocalisation. Infemination is explored through several of Kawabata's texts, with a primary focus upon his Beauty and Sadness and 'House of the Sleeping Beauties'. My separate analyses of MacDonald and Kawabata conclude with an 'atonement', an 'At-One-Ment', where the authors are united and their texts demonstrated explicitly as sharing common infeminatory desires.